Response Time Analysis of Ethernet Flows with Fixed Priority - Evaluation and Improvement of TCN Analyzer Scheduling Analysis Theory - Liu, Meng (My University, 2011)
Network response time analysis is very important in industry. For example, in the design level of a vehicle production, the designer always needs to make the scheduling analysis to ensure the safety of the designed system. At present, CAN is the most popular network used in industry, however, as the increase of the demand (e.g. link speed, flexible topologies, etc), CAN is becoming limited. Instead, Ethernet technique is more and more considered in industry. Some professional experts have developed solutions to make the response time analysis for Ethernet. But they mostly focus on EDF scheduling or FCFS queuing. In this thesis work, we focus on multi-hop analysis with fixed priority scheduling (e.g. Rate-Monotonic). And both simple periodic traffic and Generalized Multi Frame model traffic are taken into account.
Keywords: Information Technology; Informationsteknik